Chapter 4: Posthuman feminism and feminist new materialism: towards an ethico-onto-epistemology in research practices - Cozza, Michela (Edward Elgar Publishing, 2023)
Following the principles of post-humanism ("post" to the humanist universalism of "Man") and post-anthropocentrism ("post" to the exceptionalism of the human species), and by conflating them into the concept of ethico-onto-epistemology, we explore how posthumanist feminism may inform research in management and organisation studies (MOS). We propose conceiving posthuman feminism as a politics of knowledge that requires a significant departure from human-centred research methods to account for interconnections that always populate research practices and processes of knowing, being, and doing. Grounding our chapter in posthumanism and in post-qualitative feminist research, we explore the concepts of matter/mattering, decentring the subject, becoming within a research agencement, and affecting/being affected. We show how they make one another while inspiring four methodologies: diffraction, cartography, research agencement, and affective ethnography. We conclude by pointing out how posthuman feminism can contribute to change the apparatus of knowledge production in MOS through response-able research practices.